Relationship between Parents Acceptance with Effectiveness, Risk and Procedures of Provisioning Covid-19 Vaccine in Children Aged 6-11 Years in East Kolaka Regency - Hijrana, Hijrana; Kamalia, La Ode; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction: Parents acceptance of this Covid-19 vaccination is a challenge in the success of the Covid-19 vaccination program. This study was to identify the relationship between parental acceptance (Effectiveness, Risk, and Procedure for Giving the Covid-19 Vaccine). Methods: This research is a quantitative study with a Cross-Sectional Study approach. The population in this study were all children aged 6-11 years domiciled in East Kolaka Regency. The sampling technique was simple random sampling, with a sample of 369 respondents. Results: The study showed that of the 369 respondents who received the Covid-19 vaccination well, 203 (55.0%) respondents and 166 (45.0%) respondents who received poor reception. Based on statistical tests, it shows that there is a significant weak category relationship between parental acceptance and the effectiveness of giving Covid-19 vaccination (p value = 0.000) and parental acceptance with the risk of giving Covid-19 vaccination (p value = 0.000) while the variable procedure for giving Covid vaccination is (p value = 0.117) which means there is no significant relationship with parental acceptance of Covid-19 vaccination. Conclusion: Public awareness is needed to be active and participate in vaccination activities as an effort to protect themselves, their families and others. Also as a form of support for the government's efforts to suppress Covid-19 cases.